Force and flowfield measurements to understand unsteady aerodynamics of cycloidal rotors in hover at ultra-low Reynolds numbers. (February 2019) - Reed, Carolyn M; Coleman, David A; Benedict, Moble
This paper provides a fundamental understanding of the unsteady fluid-dynamic phenomena on a cycloidal rotor blade operating at ultra-low Reynolds numbers (Re ∼ 18, 000) by utilizing a combination of instantaneous blade force and flowfield measurements. The dynamic blade force coefficients were almost double the static ones, indicating the role of dynamic stall. For the dynamic case, the blade lift monotonically increased up to ±45° pitch amplitude; however, for the static case, the flow separated from the leading edge after around 15° with a large laminar separation bubble. There was significant asymmetry in the lift and drag coefficients between the upper and lower halves of the trajectory due to the flow curvature effects (virtual camber). The particle image velocimetry measured flowfield showed the dynamic stall process during the upper half to be significantly different from the lower half because of the reversal of dynamic virtual camber. Even at such low Reynolds numbers, the pressure forces, as opposed to viscous forces, were found to be dominant on the cyclorotor blade. The power required for rotation (rather than pitching power) dominated the total blade power.